Analysis Factor Risk Heavy Baby Low Birth Based On Anemia In Term Pregnancy At Harapan Clinic, West Jakarta - Retno Palupi Yonni Siwi; Elisa Handayani (Journal of Health Science Community, 2025)
Based on data profile health DKI Jakarta on year 2020 found 985 LBW in DKI Jakarta. The high incidence of LBW is caused by several factors, one of which is anemia during pregnancy. This study aims to determine the correlation between anemia and the incidence of LBW in term pregnancies at the Harapan Clinic, West Jakarta. This study used a retrospective cohort study design . Samples in study This as much as 72 Mother give birth to in Clinic Hope West Jakarta in 2022 with total sampling technique . This study uses secondary data Which taken from book register Mother pregnant in Clinic Hope Jakarta West Java period January – December 2022. Data analysis in this study used the chi square test. The results of the study showed that most respondents experienced anemia during pregnancy, as many as 43 respondents or 59.7%, with most respondents giving birth to babies who were not LBW, as many as 48 babies or 66.7%. There were 33.3% of pregnant women with anemia giving birth to LBW babies. Analysis using the Chi-Square statistical test obtained a result of p 0.000 (p value <0.05), meaning that there was connection Which significant between anemia pregnancy with incident LBW at Harapan Clinic, West Jakarta. Anemia during pregnancy can cause adverse effects on the mother and the baby she will give birth to. Anemia can reduce the oxygen supply to the mother's metabolism because hemoglobin functions to bind oxygen. The hope of this research for the community is to increase knowledge about the incidence of LBW and anemia during pregnancy.